Assessing Maternal and Fetal Risks Associated with Prolonged Induction of Labor - Triebwasser, Jourdan E.; VanArtsdalen, Jamie; Kobernik, Emily K.; Seiler, Kristian; Langen, Elizabeth S. (American Journal of Perinatology, 2019)
Objective To assess whether prolonged induction of labor was associated with increased maternal or neonatal morbidity.Study Design We performed a retrospective cohort study of women undergoing induction of labor at a single institution. We included women with singletons ≥ 36 weeks with initial cervical dilation ≤4 cm. Prolonged induction of labor was defined as lasting > 36 hours from the time of initial method to delivery. A 2-to-1 propensity score-matched analysis was performed between women with and those without prolonged induction of labor. Maternal outcomes were cesarean delivery, chorioamnionitis, endometritis, postpartum hemorrhage, severe perineal laceration, and length of postpartum admission. Neonatal outcomes included Apgar scores, umbilical artery pH, and neonatal intensive care admission.Results Among 2,021 women, 407 (20.1%) had a prolonged induction. In unadjusted analyses, prolonged induction of labor was associated with increased cesarean delivery and chorioamnionitis. After 2-to-1 propensity score matching, there were 267 women with prolonged induction and 424 controls. Women with prolonged induction of labor had higher rates of cesarean delivery (35.6 vs. 16%, p < 0.001), chorioamnionitis (14.2 vs. 4.7%, p < 0.001), endometritis (6.4 vs. 1.9%, p = 0.002), and postpartum hemorrhage (18.8 vs. 11.9%, p = 0.008). There were no significant differences in neonatal outcomes.Conclusion Overall length of induction impacts maternal outcome.
Keywords: obstetrics; labor induction; maternal complications; neonatal outcomes